Effect of Dried Sweet Corn Cake Powder Substitution on Quality of Cookies - Sopa, Bongkochmas; Fudsiri, Saowanee; Kongphapa, Juthamas (Burapha Science Journal, 2025)
Background and Objectives : The sweet corn milk product from the National Corn and Sorghum Research Center is widely popular among people of all ages due to its unique aroma and pleasing taste. This has resulted in a large quantity of sweet corn milk being produced and released into the market, leading to a significant amount of corn residue, which is a by–product of the production process. The manufacturer sells this corn residue to be used as animal feed, amounting to approximately 900–1,000 kilograms per day. Therefore, to increase the value of agricultural by–products and reduce the use of wheat flour, while also enhancing the nutritional value of the developed products. The objective of this research is to investigate the optimal utilization of wheat flour supplemented with dried sweet corn cake (DSCP) in cookies. The ideal amount of sweet corn residue accepted by consumers was determined in this study. Methodology : Sweet corn cake powder was prepared by drying fresh sweet corn cake in a hot air oven at 70 degrees Celsius for 24 hours, then grinding and sieving it into a fine yellow powder. The DSCP is analyzed for its physicochemical properties, including color value, beta-carotene content, total phenolic content, and antioxidant activity using the DPPH and ABTS free radical scavenging assay methods. Before using the DSCP to replace wheat flour in cookies, a basic recipe for cookie production was selected. This was done by evaluating five different cookie recipes using sensory evaluation with 50 general panelists as testers. The basic recipe that received the highest overall liking score from the panels was further developed into a cookie recipe by replacing wheat flour with DSCP. Utilization of DSCP for replacing wheat flour by 25, 50, 75 and 100% (w/w) of total flour in cookie were studied. The effect of DSCP supplementation on physical and chemical characteristics, including width, thickness, spread ratio, hardness, color value, water activity, proximate analysis (moisture, protein, fat, ash, carbohydrates and dietary fiber), beta-carotene content, total phenolic content and antioxidant activity were measured using the DPPH and ABTS free radical scavenging assays. The sensory quality attributes of the cookies were evaluated, including overall acceptance, appearance, color, taste, texture, and flavor. Main Results : The dried and finely ground sweet corn residue powder was found to have lightness (L*), redness (a*), and yellowness (b*) values of 77.39, 7.68, and 37.83, respectively. The chroma (C*) value was 38.60, the hue angle (h°) was 78.51, which corresponds to a color range from orange-red to yellow and color different ( E) was 16.30. Additionally, the DSCP contained beta-carotene at 350.52 µg/100 g, a total phenolic content of 55.36 mg GAE/100 g DW and antioxidant activities measured by the DPPH and ABTS methods at 94.48 and 44.72 mg TE/100 g DW, respectively. For the results of the basic cookie selection, it was found that the basic cookie recipe formula 4 had higher liking scores of all sensory characteristics than other formulas. The main ingredients of the optimum basic formulation of cookie products included all–purpose wheat flour, sugar, salted butter, eggs, baking powder and baking soda at 27.18%, 27.18%, 36.35%, 8.95%, 0.23 and 0.11%, respectively. Therefore, the basic formula 4 was selected to study the optimum level of wheat flour replacement with sweet corn cake powder. It was found that adding DSCP to the cookies had no significant effect on width, thickness, or spread ratio (p>0.05), except for hardness and water activity which increased with the substitution level (p≤0.05). Additionally, the cookies showed a decrease in lightness, while redness and yellowness values increased significantly (p≤0.05). The chroma value and E increased, while the hue angle decreased as the substitution level of DSCP increased, ranging from 63.92 to 75.36, indicating a color range from orange-red to yellow. The proximate results of the cookies showed an increase in moisture content (2.00–3.39%), protein (5.95–8.60%), fat (28.67–32.22%), ash (1.08–2.01%) and total dietary fiber (1.14–8.64%) as well as decrease in carbohydrate (63.32–53.79) as substitution level of DSCP increase (p£0.05). Furthermore, the cookies also showed a significant increase in beta–carotene content, total phenolic content and antioxidant activity when analyzed using the DPPH and ABTS assays (p£0.05). The results from sensory evaluation showed that the sample containing 25% DSCP had no difference of overall linking score comparable to the control (p>0.05). Conclusions : The optimal substitution ratio of DSCP for wheat flour was 25%, as the overall liking score was not significantly different from the control sample (p>0.05). This formulation exhibited a lightness of 57.28, redness of 6.51, yellowness of 18.04, chroma of 21.88 and hue angle of 71.93, indicating a color range from orange-red to yellow. The chemical compositions of cookies with 25% DSCP consist of moisture, protein, total fat, ash, total carbohydrate and total dietary fiber at 2.47, 6.77, 29.58, 1.27, 59.92 and 2.28%, respectively. Beta-carotene and total phenolic content were 55.59 µg/100g sample and 98.62 mg GAE/100g DW, respectively. Furthermore, the DPPH and ABTS radical scavenging activities were 12.59 and 35.16 mg TE/100g DW, respectively. It could be concluded that the use of DSCP had potential to enhance the nutritional and antioxidant potential of cookies.